Population genetic results of Hungarian Botrytis cinerea isolates establishing new technologies with decreased chemical usage against grey mould - Sándor, Erzsébet (Acta Agraria Debreceniensis, 2012)
Botrytis cinerea causes gray mold on a high number of crop plants. Information about the populations of plant pathogen fungi may help to develop new strategies for the effective and economic crop protection with reduced fungicide usage. Hungarian B. cinerea populations were characterized with using different molecular genetic parameters. B. cinerea group I strains, characterized with high rate of fenhexamid resistance, could be detected only in restricted number. The Hungarian B. cinerea populations were characterized with high genetic diversity, and the regular occurrence of sexual reproduction. These results highlight the importance of rotating different type of fungicide in the plant protection technology against grey mould.